Influência dos sistemas exclusivo e integrado de produção e dos estádios fenológicos da soja nas comunidades bacterianas do solo - Santos, Jussane Antunes Fogaça dos (2021)
Plant growth and productivity depend on the interaction of plants with soil microorganisms for nutrient availability, growth promotion and protection against pathogens. Studies about the influence of soybean phenological stages and the environment which it is inserted in soil bacterial communities have already been reported, however, there are still no studies that address the influence of integrated production systems in these communities. In this study, the structure of soil bacterial communities in the rhizosphere and bulk soil was evaluated over eight phenological stages of soybean (Glycine max) cultivated in an Exclusive Production System and Crop-Livestock-Forest Integration. The Proteobacteria phyla followed by Actinobacteriota and Acidobacteriota were the most abundant in all soybean growth stages in the rhizosphere and bulk soil of the systems. This study reveals that the phenological stages modulate the structure of bacterial communities in the rhizosphere and in the evaluated bulk soil and that the systems can influence the microbial richness.